2016
DOI: 10.1093/sleep/zsw058
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality and Nocturnal Sleep Duration in Pregnancy and Risk of Gestational Diabetes Mellitus

Abstract: During pregnancy, Asian women with poor sleep quality or short nocturnal sleep duration exhibited abnormal glucose regulation. Treating sleep problems and improving sleep behavior in pregnancy could potentially reduce the risk and burden of GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(86 citation statements)
references
References 64 publications
1
83
1
1
Order By: Relevance
“…[8, 9] Data from pregnancy cohorts, both prospective and retrospective, using self-reported sleep duration have also suggested that short sleep is a risk factor for GDM. [3537] In one study of 63 pregnant women who wore an actigraph in mid-pregnancy, objectively measured short sleep was associated with higher values on 1-hour GTT screening tests. [21] Our data are consistent with and extend the findings of these previous reports, confirming that short sleep duration, as objectively measured by actigraphy, is associated with incident GDM in a large population of nulliparous women.…”
Section: Discussionmentioning
confidence: 99%
“…[8, 9] Data from pregnancy cohorts, both prospective and retrospective, using self-reported sleep duration have also suggested that short sleep is a risk factor for GDM. [3537] In one study of 63 pregnant women who wore an actigraph in mid-pregnancy, objectively measured short sleep was associated with higher values on 1-hour GTT screening tests. [21] Our data are consistent with and extend the findings of these previous reports, confirming that short sleep duration, as objectively measured by actigraphy, is associated with incident GDM in a large population of nulliparous women.…”
Section: Discussionmentioning
confidence: 99%
“…Current data suggest that poor sleep quality is associated with an enhanced proinflammatory profile 22 and preterm birth 23 as well as an increased risk of metabolic outcomes. 24 Hence, conditions that result in poor sleep such as RLS, as demonstrated in this study, become critical to identify and possibly important to treat pharmacologically. The research by Dunietz et al 18 and others 14 elevate the diagnosis of RLS in pregnancy from a self-limited condition that would likely resolve postpartum to one with potential adverse obstetric events and beg for studies evaluating the efficacy and outcome of treating RLS in pregnancy.…”
Section: Commentary Shaking Up Perspectives Of Restless Legs Syndromementioning
confidence: 87%
“…These items are scored from 0 to 3, and then added together to calculate a total PSQI global score ranging from 0 to 21. It was reported in past studies that the PSQI has similar psychometric properties in both non-pregnant populations and pregnant women [26]. The PSQI has been used on pregnant Asian women in previous studies [26][27][28].…”
Section: Salivary Melatonin and Cortisol Rhythmmentioning
confidence: 99%
“…It was reported in past studies that the PSQI has similar psychometric properties in both non-pregnant populations and pregnant women [26]. The PSQI has been used on pregnant Asian women in previous studies [26][27][28]. A validated Malay version of PSQI will be used in the study [29].…”
Section: Salivary Melatonin and Cortisol Rhythmmentioning
confidence: 99%